Physiotherapy Management in Recovery of Post Op Amputation Below Knee Sinistra - Sri Khofifah Farina Zukhaeri; Syi’ar Aprilla Tanazza (Jurnal Kesehatan dan Fisioterapi, 2023)
Feet are a means of movement that have an important role in carrying out activities. These activities include standing, walking, running, moving around and other functional activities. Removal of limbs which involves cutting off part or all of a limb is generally amputation caused by accidents, congenital disorders and diseases, including Peripheral Artery Disease (PAD). Physiotherapy examinations that can be carried out in this situation include pain examination using the VDS scale, muscle strength examination using MMT, joint range of motion examination using a Goniometer and functional activities. The modalities used in this condition are TENS, ES (Electrical Stimulations), and exercise therapy. The results showed that there was progress towards improvement even though it was still in the minimal category.Keywords: Amputation, Intervention, Physiotherapy, Rehabilitation